Challenges in better coordinating Tokyo's urban rail services - Hironori Kato (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2016)
This paper describes Tokyo's urban rail market, which has traditionally been privately funded and operated; and discusses policies aimed at better coordinating public transport services. Although the industry has delivered high quality infrastructure and services for most users, the existence of many different private operators and owners of tracks means that services and station facilities are not always well connected to one another. Individual private parties often lack sufficient incentives to invest in connectivity improvements, such as installing elevators in stations or implementing missing connections between lines, since these do not usually directly increase their profits. Three case studies explore different policy responses to the challenge of balancing competing wishes of private actors with the needs of travellers. In all cases the government has intervened through legislation and grants to try to stimulate connectivity investment and to do so in consultation with local communities. The recent government interventions into the Tokyo rail market represent a gradual evolution in market structure with the goal of better meeting social needs.
Keywords: 330; Schienenpersonennahverkehr; Nahverkehrspolitik; Tokio; Japan